Instrument for Assessing Surgical Skills Related to Performing a Vascular Anastomosis - Buril, Gabriela de Oliveira; Carvalho, Joseph Monteiro de; Nunes-Nogueira, Vania dos Santos [UNESP] (Soc Brasileira Angiologia Cirurgia Vascular-sbacv, 2025)
Technical skill is one of the most important components of surgical competence and must be thoroughly learned and developed over the course of surgical residency. However, there are still few instruments for directly appraising and quantifying surgical skill and the majority of centers rely on the subjective observations of tutors. The objective of this study was to conduct a scoping review on the subject of instruments for appraisal of surgical skills available for assessment of vascular anastomosis performed by vascular surgery residents. A review was conducted using the following search terms: educational measurement, vascular surgery, and internship and residency. The initial search results comprised 616 articles. After application of the eligibility criteria, just four studies were included in the review, only one of which was conducted in Brazil. Three of the studies used Objective Structured Assessment of Technical Skill (OSATS) to assess residents. However, all used separate and different supplementary checklists for evaluation of specific skills related to anastomoses. Appropriate appraisal and precise feedback during residency training are an extremely important part of residents' training. Systematic and objective feedback enables errors to be corrected and skills to be polished. Since there is no instrument for assessment of the surgical skills needed to perform anastomosis, after completion of the review a rating instrument was proposed focused on this important skill that vascular surgery residents must acquire. The instrument comprises a compilation of the instruments reviewed and includes a proposed checklist for use in real-world settings.
Keywords: educational measurement; vascular surgery; internship and residency